THE LITERARY APPRECIATION OF DRAMA APPLIES SEVEN READER RESPONSE STRATEGIES TO ENCOURAGE STUDENTS' LITERACY ABILITY THROUGH LESSON STUDY - Rulik Setiani; Elis Susanti; Darwanto (Edupedia Publisher, 2023)
The aim of the research is find out seven reader response strategies can encourage students’ literacy ability through lesson study. The method of research is Lesson Study-based Action Research. While the subjects in the action research in this lesson study are the fifth semester students of English education study program which consist of 28 students. The instruments used are observation and test. The data used in this study are qualitative and quantitative data. Related to the result of students score in cycle one shows that there are 3 students who categorized in very good, 10 students who categorized in good, 15 students who categorized in enough, and there were not categorized in poor and very less. Based on the result of observation and students score have not good enough categorized so it needed improvement on the next stage or next cycle that is second cycle. Related to the result of students score in cycle one shows that there are 10 students who categorized in very good, 13 students who categorized in good, 5 students who categorized in enough, and there were not categorized in poor and very less. Based on the result of observation and students score have mostly very good and good categorized so it means that there are improvement from cycle one to cycle two.